EFL STUDENTS’ PERCEPTION OF THE LECTURERS’ COMPETENCE BASED ON THEIR BACKGROUND - Nunung Anugerawati Syam (Universitas Muhammadiyah Makassar, 2016)
This study aimed at finding out and describing (1) how the EFL students perceive the lecturers’ competence viewed from their educational qualifications (Bachelor, Master, Doctor, or Professor), (2) how the EFL students perceive the lecturers’ competence viewed from their personal background in terms of age (young and old), and (3) how the EFL students perceive the lecturers’ competence viewed from their personal background in terms of gender (male and female). The results of the research are expected to give meaningful information to the readers, particularly the students, about how to behave and communicate well with the lecturers without paying attention to their background. The research findings showed that the students perceived the lecturers with Master degree are more competence and have a good person rather than lecturers with Bachelor Degree and Doctorate Degree viewed from their educational background. If they are viewed from their personal background in terms of age and gender, students perceived that male and young lecturers are more competence than female and old lecturers, but female and old lecturers have a better personality than male and young lecturers. Keywords: Perception, competence, educational and personal background